KEBIASAAN MAKANAN IKAN BAUNG (Mystus nemurus C.V) di Sungai Bingai Kota Binjai Provinsi Sumatera Utara Food Habit of Baung Fish (Mystus nemurus C.V) in Bingai River Binjai City, North Sumatera Province - windy windy; Hesti Wahyuningsih; Ani Suryanti (AQUACOASTMARINE, 2015)
Research of Baung’s food (Mystus nemurus C.V) was performed in Bingai river in June to August 2014. The purpose of this study was to determine the type of natu-ral food and the availability of natural forage baung (Mystus nemurus CV) in the Bingai River and general condition of the waters of the Bingai. Stomach contents were analyzed by using Index of preponderance. Stomach contents consisted of 8 types of fish, plant fibers, Thiara scabra, Planaria sp., Nodilittorina pyramidalis, Faunus ater, the rest of the insect, and coupled with parts not identified. The small fish is the main food, fiber plants is a complementary food, and Planaria sp., Thiara scabra, Nodilittorina pyramidalis, and Faunus ater are additional food. Benthos as natural food in the bottom waters which have the highest abundance was Thiara scabra. Baung selective about its food. Index of Electivity (E) indi-cates that Planaria sp. is a popular type of fish food benthos baung than other benthos.Keywords: Bingai river, Food habit, Mystus nemurus.